2011
DOI: 10.3934/dcdss.2011.4.1267
|View full text |Cite
|
Sign up to set email alerts
|

Persistent mobile lattice excitations in a crystalline insulator

Abstract: We examine tracks in crystals of muscovite of high energy charged particles, and of mobile lattice excitations created by kinetic atomic scattering. The mobile lattice excitations are interpreted as a type of breather, here called a quodon. The typical energy of a quodon can be found from the decay of potassium K 40 atoms in the crystal and supports their interpretation as a type of breather. In turn, this establishes a unique signature for energetic quodons, the 'kinked-line' tracks, allowing discrimination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Related studies of trapping of charge by mobile anharmonic excitations in 2D arrays added credence to this suggestion [8][9][10]. Numerical modelling and analogue studies of simplified muscovite lattices showed that quodons could be longitudinal breathers [11][12][13][14]. The propagation Å with h = 4.…”
mentioning
confidence: 81%
“…Related studies of trapping of charge by mobile anharmonic excitations in 2D arrays added credence to this suggestion [8][9][10]. Numerical modelling and analogue studies of simplified muscovite lattices showed that quodons could be longitudinal breathers [11][12][13][14]. The propagation Å with h = 4.…”
mentioning
confidence: 81%
“…The molecular dynamics simulation has also been attempted by assuming the thermal spike to account for the hillock formation mechanism [28]. Although the mechanism of the phenomena has been debated for several decades, it is still a matter of controversy [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Detailed characterization of hillocks created by SHI irradiation is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…The motion of slowly moving ballistic positive charges should also create fossil tracks composed of magnetite. The first notable feature of these tracks was their exceptional length, of up to 40 cm, limited by size of the crystal [13]. The second feature was their propagation in any of the six principal crystallographic directions in the excellent insulator muscovite in absence of an applied electromotive force (emf) [13].…”
Section: A the Study Of Fossil Tracks In Muscovite Crystalsmentioning
confidence: 99%
“…The first notable feature of these tracks was their exceptional length, of up to 40 cm, limited by size of the crystal [13]. The second feature was their propagation in any of the six principal crystallographic directions in the excellent insulator muscovite in absence of an applied electromotive force (emf) [13]. The third surprising feature was that the tracks were formed when the crystal was cooling at a temperature exceeding 700 K, indicating non-interaction of the mobile excitation with phonons [11].…”
Section: A the Study Of Fossil Tracks In Muscovite Crystalsmentioning
confidence: 99%